2017
DOI: 10.1080/03601234.2017.1356668
|View full text |Cite
|
Sign up to set email alerts
|

Herbicidal activity of slow-release herbicide formulations in wheat stands infested by weeds

Abstract: The present study reports the herbicidal activity of metribuzin and tribenuron-methyl embedded in the degradable matrix of natural poly-3-hydroxybutyrate [P(3HB)/MET and P(3HB)/TBM]. The developed formulations were constructed as films and microgranules, which were tested against the weeds such as white sweet clover Melilotus albus and lamb's quarters Chenopodium album in the presence of soft spring wheat (Triticum aestivum, cv. Altaiskaya 70) as the subject crop for investigation. The activity was measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…34 Other research showed the efficacy of slow-release formulations in wheat plant communities contaminated with weeds. 35 However, because of the relatively high cost of PHAs and the extensive use of pesticides in agriculture, a more effective approach is to blend available natural materials with PHAs rather than to use PHAs alone. Moreover, this approach corresponds to the concept of industrial ecology and 'green' chemistry, focused on deriving new available materials from renewable sources.…”
Section: Etcmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Other research showed the efficacy of slow-release formulations in wheat plant communities contaminated with weeds. 35 However, because of the relatively high cost of PHAs and the extensive use of pesticides in agriculture, a more effective approach is to blend available natural materials with PHAs rather than to use PHAs alone. Moreover, this approach corresponds to the concept of industrial ecology and 'green' chemistry, focused on deriving new available materials from renewable sources.…”
Section: Etcmentioning
confidence: 99%
“…Slow‐release formulations of the ‘Zellek Super’ herbicide loaded into films and microgranules of P(3HB‐co‐3 HV) were prepared and investigated by a team of researchers , showing effective suppression of model weeds . Other research showed the efficacy of slow‐release formulations in wheat plant communities contaminated with weeds . However, because of the relatively high cost of PHAs and the extensive use of pesticides in agriculture, a more effective approach is to blend available natural materials with PHAs rather than to use PHAs alone.…”
Section: Introductionmentioning
confidence: 99%
“…The present study builds on our previous work, 13 where DCD was extruded as a composite material within a biodegradable polymer matrix, namely poly(3‐hydroxybutyrate‐ co ‐3‐hydroxyvalerate) (PHBV). This bacterial polyester has been studied extensively for the controlled release of drugs, 14–16 food packaging additives 17 and agrichemicals 18–22 due to its ability to slow the rate of water diffusion, biocompatibility and biodegradability in almost any environment, including soils, fresh water systems and oceans. Our previous study revealed that, at loading of 250 g kg −1 mobilization of DCD from the PHBV matrix occurs via four distinct mechanisms: (i) initial rapid dissolution of surface available DCD, (ii) channelling of water through voids and pores in the PHBV matrix, (iii) gradual diffusion of water and DCD through layers of PHBV, and (iv) biodegradation of the PHBV matrix 13 .…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies described P(3HB) microparticles, granules, films, and pellets loaded with the herbicide metribuzin and the fungicide tebuconazole; release kinetics of the active ingredients and degradation of the polymer matrix were investigated in soil microecosystems [15][16][17]. The efficacy of the formulations was evaluated in laboratory wheat ecosystems contaminated with weeds and infected with fusarium pathogens [18][19].…”
Section: Introductionmentioning
confidence: 99%